THE EFFECT OF INTERNAL COMMUNICATION SATISFACTION, ORGANIZATIONAL CULTURE AND BENEFITS ON ORGANIZATIONAL IDENTIFICATION IN SYIFA MEDIKA GENERAL HOSPITAL - Hongdiyanto, Charly; Saidah, Naila (PERFORMA, 2024)
The turnover of Syifa Medika General Hospital is increasing every year since 2019 to 2021. To solve this problem, the researcher would like to give insight for the company to be more concerned of the sense of belonging (organizational identification) in employees because when an employee already have a high level of organizational identification, they will be much more careful in taking decisions and work genuinely for the company which will increase the work performance in order to make a success for the company. Therefore, this study will examine the factors that influence organizational identification (normally called as sense of belonging). The population of this research will consist of individuals who work in Syifa Medika General Hospital, and the sample of this research is 187 respondents. To collect the research data, the researcher will spread 187 questionnaires by online survey using google form. to all of the departments’ employees that have met the requirements for filling the questionnaire. This research was conducted using SmartPLS which resulted in the calculation that Internal Communication Satisfaction, Organizational Culture and Benefits had an effect on Organizational Identification in Syifa Medika General Hospital.